Buddhist Manuscript Cultures in Premodern Japan - Lowe, Bryan D. (Religion compass, 2014)
Recent discoveries and scholarship on Japanese Buddhist manuscripts have illuminated new areas of research and raised previously unexplored questions in Buddhist studies and East Asian religions. This article introduces some of the recent finds and approaches to these materials. It focuses on three sets of sources: scriptorium documents from an imperial treasure house known as the Shōsōin, canonical manuscripts (issaikyō) based on texts translated or composed in China, and sacred works (shōgyō) produced and collected by Japanese monks for use in temple life. In addition to surveying these sources and the most influential secondary literature on them, this article proposes methodological alternatives to philological studies by focusing on what I call ritual, curricular, social, and material approaches.